Hamimaera thijsseni Hughes, 2016, sp. nov. - Hughes, Lauren E. (Zenodo, 2016)
Hamimaera thijsseni sp. nov. (Figs 21–23) Type material. Holotype male, 12 mm, dissected, 4 slides, SAMA C8498, northwest of West Island, Franklin Island, Nuyts Archipelago, South Australia (32°30′35″S 133°15′7″E), intertidal rock pools, 24 February 1983, coll. W. Zeidler, P. Aerfeldt and party. Paratypes 4 specimens (2 male and 2 female), SAMA C6501, northwest of West Island, Franklin Island, Nuyts Archipelago, South Australia (32°30′35″S 133°15′7″E), intertidal rock pools, 24 February 1983, coll. W. Zeidler, P. Aerfeldt and party. Type locality. Northwest of West Island, Franklin Island, Nuyts Archipelago, South Australia (32°30′35″S 133°15′7″E). Etymology. Named to honour the Dutch Captain of the Gulden Zeepeart Francois Thijssen, who accurately mapped the South Australian coast in 1627, including the Nuyts Archipelago. Description. Based on holotype male, 12 mm, SAMA C8498. Head . Eyes subovate; lateral cephalic lobe broad, rounded, apically rounded, anteroventral margin with notch/ slit, anteroventral corner subacute. Antenna 1 longer than antenna 2; peduncular article 1 shorter than article 2, with 1 robust seta on posterior margin; peduncular article 2 longer than article 3; flagellum articles as long as broad, or broader than long, with 33 articles; accessory flagellum short, significantly less than half length of primary flagellum, with 5 articles. Antenna 2 peduncular article 4 longer in length than article 5; flagellum with 11 articles. Mandible accessory setal row, well developed with 5 setae; palp well developed, article 1 length 1.1 × width, shorter than article 2; article 2 longer than article 3, with many slender setae; article 3 rectilinear, long, 3 × as long as broad, longer than article 1, with 5 apical slender setae. Lower lip unknown. Maxilla 1 inner plate subquadrate, with 3 apical plumose setae. Pereon . Gnathopod 1 coxa anterior margin concave, anteroventral corner produced, acute, posteroventral corner with notch; merus with acute posteroventral corner; carpus length 1.9 × width, 1.1 × propodus length, setae covering medial surface; propodus subquadrate, medial surface setal comb absent; palm subacute, straight, entire, lined with robust setae, defined by posterodistal corner; dactylus closing along palm. Gnathopod 2 asymmetrical; larger gnathopod , chelate coxa posteroventral corner without notch; basis broad, anterodistal corner subquadrate, with distal long slender setae; merus with subquadrate posteroventral corner; carpus compressed, length 0.9 × width, anterior margin with long robust setae, posterior margin with rows of long slender setae; propodus rectilinear, length 1.4 × width, margin with rows of slender setae, palm angle obtuse, margin sculpted, lined with robust setae, palm defined by posteroventral corner with tooth dactylus closing along and reaching end of palm, posterior margin with proximal hump , lined with setules, unguis absent. Gnathopod 2 smaller gnathopod basis slender, anterodistal corner subquadrate; merus with subquadrate posteroventral corner; carpus subtriangular, length 2.0 × width, margins with long slender setae; propodus rectilinear, margin with rows of long slender setae, palm angle subacute, margin smooth, lined with robust setae defined by posteroventral corner; dactylus closing along and reaching end of palm, unguis present. Pereopods 5–7 slender distally; basis weakly expanded, posterior margin straight, weakly serrate, with long slender setae; merus and carpus slightly broadened; dactylus unguis simple. Pleon. Pleonites 1–3 dorsally smooth. Epimera 1–2 posterodistal corner with weak notch and small tooth. Epimeron 3 posterior margin smooth, corner with small tooth. Urosomites 1–3 without carina. Uropod 1 peduncle with 1 basofacial seta, peduncle length 1.1 × outer ramus; inner ramus longer than outer ramus. Uropod 2 peduncle length subequal to outer ramus; inner ramus longer than outer ramus. Uropod 3 rami subequal in length, longer than peduncle, length 1.5 × width, distally truncated, with lateral and apical long and short robust setae. Telson deeply cleft, length subequal to width, lobes divergent, tapering distally, apical cusp subequal, apically acute, margins concave, each lobe with 2 short apical robust setae, with 3 pair of robust setae on inner margins, and 1 pair lateral robust setae . Variation. Material includes three males, where two specimens have an enlarged gnathopod 2 on the left and one male specimen has an enlarged gnathopod 2 on the right. Remarks. Hamimaera thjisseni sp. nov. differs from H. hamigera by the more obtuse dominant gnathopod 2 propodus palm angle and the presence of inner and lateral robust setae on the telson, where the latter species has the palm tending to be more transverse and only apical robust setae. The presence of a proximal hump on the posterior margin of the male dominant gnathopod 2 dactylus further defines H. thjisseni sp. nov. Hamimaera thjisseni sp. nov. is similar to two other southern Australian maerid L. daveyi sp. nov. and L. zeidleri which also have an obtuse gnathopod 2 propodus palm on the dominant side. These species can be separated based on the epimeron 3 posterior margin, which is smooth with distal notch in H. thjisseni, while in both L. daveyi and L. zeidleri has the posterior margin is serrate. Distribution. South Australia. Nuyts Archipelago (current study); Sellicks Beach (Krapp-Schickel, 2008). : Published as part of Hughes, Lauren E., 2016, New genera, species and records of Maeridae from Australian Waters: Austromaera, Ceradocus, Glossomaera, Hamimaera, Huonella gen. nov., Linguimaera and Maeraceterus gen. nov. (Crustacea: Amphipoda), pp. 1-81 in Zootaxa 4115 (1) on pages 33-36, DOI: 10.11646/zootaxa.4115.1.1, http://zenodo.org/record/255539 : {"references": ["Krapp-Schickel, T. (2008) What has happened with the Maera - clade (Crustacea, Amphipoda) during the last decades? Bolletino del Museo Civico di Storia Naturale di Verona, 32, 3 - 32."]}